My culture, my plate : an exploration of the cultural food and meal preferences of Māori, Pacific, and Chinese groups during hospital admission in New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science majoring in Nutrition and Dietetics, Massey University, Auckland, New Zealand - Esau, Kim (Massey University, 2020)
Background: There has been a rapid surge in the number of Indigenous Māori, Pacific and Chinese people residing in New Zealand (NZ). This influx in both indigenous and other ethnic minority groups generates a demand for culturally appropriate healthcare services, particularly within the hospital setting. Since hospital foodservice satisfaction contributes to overall patient satisfaction, it is important that the cultural food preferences of these ethnic groups are taken into account when developing or revising NZ hospital menu standards. Aim: This study explores the cultural food preferences of Māori, Pacific and Chinese (MPC) adults residing in NZ when unwell and during hospital admission. Methods: This exploratory, mixed-method study was conducted in four phases. Forty-four participants, 18+ years, hospitalised within the past year and of MPC ethnicity were recruited to participate in this study. A self-administered, semi-structured exploratory survey and three ethnic-specific focus groups and one combined ethnicity focus group from recruited participants, were used to explore the cultural food preferences and hospital foodservice experiences of MPC population groups. Descriptive statistics were used for the analysis of the quantitative survey results, and the framework data analysis method was employed for the analysis of the qualitative focus group data. Results: The current menu for NZ public hospitals was not considered culturally appropriate by the majority of MPC participants, with the lack of cultural foods, poor menu variety, small food portions and cold food temperatures identified as significant concerns. Although the majority of MPC participants had most of their meals supplied by the hospital, hardly anyone reported finishing their hospital meal at any point in time and most were supplied with family-made meals. The most disliked meal was breakfast, including cold toast and cereal, and the most enjoyed meal across ethnic groups was dinner, with favoured meals being chicken-based dishes. MPC population groups expressed a strong preference for cultural foods when unwell or in hospital. This preference was retained despite evidence of dietary acculturation following exposure to western dietary patterns a) since colonization for Māori and b) upon migration to NZ for Pacific and Chinese groups. A variety of MPC cultural food preferences were identified as appropriate for hospital menu incorporation: for Maori and Pacific, starchy vegetables (e.g. taro, kumara) and seafood (e.g. fish, mussels); for Māori, fried bread and boil-up; for Pacific, chop suey and supo povi / pisupo; for Chinese, rice-based dishes and thin soups (e.g. congee and chicken soup). Food textures and temperatures were also of great importance to Chinese groups, as hot, liquid-based foods were prescribed by their Traditional Chinese Medicine (TCMM) practices when unwell. For all ethnic groups, cultural food preferences contribute to their identity, health and wellbeing. Conclusion: Foodservices within public hospitals can be improved to sufficiently meet the cultural needs of MPC groups residing in NZ. The MPC cultural food preferences and hospital foodservice improvement suggestions from this research study may be used for future menu developments and reviews of the National Nutrition Standards in NZ public hospitals. Providing culturally-appropriate meals in hospital would improve the hospital experience and foodservice satisfaction levels for MPC populations residing in NZ.
Keywords: 321005 Public health nutrition